Pengaruh Profesionalisme Dan Disiplin Kerja Terhadap Mutu Pendidikan SD TPI Gedangan - Khoirun Nisak; Muhamad Ramdhan; Rachman Upe (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
The purpose of this study is to determine the influence of professionalism and work discipline on the quality of education at SD TPI Gedangan. The research method used in this study is Descriptive Associative with a quantitative approach. The population is 40 people. The sampling technique uses saturated samples so that the number of samples in this study is 40 respondents. The data analysis technique uses multiple regression. The results of the study show that: (1) Professionalism has a positive and significant effect on the quality of education at SD TPI Gedangan, with a ttable > tcount value of 5,656 > 2,026 with significance = 0.000 which is below 0.05. (2) Work Discipline has a positive and significant effect on the quality of education at SD TPI Gedangan, with a ttable > tcount value of 3,962 > 2,026 with significance = 0.000 which is below 0.05. (3) Professionalism and Work Discipline together have a positive and significant effect on the quality of education at SD TPI Gedangan, with a value of Fcal > a value of Ftable which is 16,128 > 3.25, with a significance = 0.000 which is below 0.05.